Crystallization of the recombinant endonuclease EndoG from Leishmania (Viannia) panamensis (2015)
ABSTRACT: Endonuclease G (EndoG) is an enzyme that specifically cleaves double stranded DNA at the dG and dC positions and has been shown to participate in chromatin degradation during apoptosis in Leishmania. The main goal of this work was to purify and crystallize EndoG in preparation for future structural studies that will permit a detailed understanding of the function of this enzyme. Materials and methods: EndoG protein was puri ed using Ni-af nity chromatography under denaturing conditions, then refolded in vitro and crystallized by the hanging-drop vapor diffusion method. Results and conclusion: The endonuclease G protein from Leishmania (viannia) panamensis was overexpressed, refolded, purified and demonstrated to be enzymatically active. Here, we reports the first successful crystallization of the EndoG protein in this group of protozoan parasites. The protein was crystallized by the hanging-drop vapor diffusion method. High quality EndoG crystals were obtained that perhaps will permit determination of the three-dimensional structure of EndoG using X-ray diffraction.